СУБЪЕКТЫ ПРОВЕДЕНИЕ СЛЕДСТВЕННЫХ (РОЗЫСКНЫХ) ДЕЙСТВИЙ, ОГРАНИЧИВАЮЩИХ НЕПРИКОСНОВЕННОСТЬ ЖИЛИЩА ИЛИ ИНОГО ВЛАДЕНИЯ ЛИЦА - Салманов, Алексей Валерьевич (SUPREMANCE OF LAW, 2017)
The article analyzes scientific approaches to the interpretation of the term “subject” and its relationship with related concepts in criminal procedural science. It is proposed, under the subjects of investigative (search) actions, limiting the inviolability of the home or other possession of a person, to understand persons who, on the basis and in the manner determined by the criminal procedural legislation of Ukraine, enter into procedural legal relations in connection with the conduct of a set of cognitive and search actions related to penetration into a dwelling or other possession of a person, in order to obtain and verify evidence and information about them. Depending on the procedural interest, it is proposed to distinguish between the subjects of the production of investigative (search) actions that limit the inviolability of the home or other possession of a person, who protect public interests or protect personal interests.
Keywords: investigative (detective) action; restrictions; inviolability of home or other possession of a person; subjects; criminal proceedings; criminal procedural legislation